USE OF FACTORIAL DESIGN TO OPTIMIZE THE EFFICIENCY OF BACTERIAL TRANSFORMATION - MENGHIU, Gheorghița; ZBÎRCEA, Lauriana-Eunice; OSTAFE, Vasile (Studia Universitatis Babeș-Bolyai Chemia, 2019)
A Plackett-Burman factorial design of experiments was created to optimize the protocols of preparation of E. coli DH5α competent cells and transformation of these cells by heat shock method using a chiA_pUC57 plasmid. The numerical parameters to be optimized were: the pH, the concentration of CaCl2, the cell concentration of the culture used for the preparation of the competent cells, the temperature of defrosting of the competent cells, the concentration of plasmid DNA. It was also considered a qualitative factor that might influence the transformation efficiency, namely the use of ultrasound in the heat shock step of transformation protocol. A design of experiments based on 26 experimental values was created. Analyzing this experimental setup by both, Plackett-Burman factorial design and surface response design, it was highlighted that the pH, the concentration of calcium chloride and the concentration of plasmid DNA have a significant influence on the transformation efficiency. The optimal conditions for the preparation and transformation of E. coli DH5α competent cells with chiA_pUC57 plasmid where when the pH of a 40 mM CaCl2 solution was 6, the competent stock cells were thawed slowly on ice and in the heat shock step the cells were subjected to ultrasounds treatment.